Two Geminin homologs regulate DNA replication in silkworm, Bombyx mori. Issue 9 (3rd May 2017) - Tang, Xiao-Fang; Chen, Xiang-Yun; Zhang, Chun-Dong; Li, Yao-Feng; Liu, Tai-Hang; Zhou, Xiao-Lin; Wang, La; Zhang, Qian; Chen, Peng; Lu, Cheng; Pan, Min-Hui
ABSTRACT: DNA replication is rigorously controlled in cells to ensure that the genome duplicates exactly once per cell cycle. Geminin is a small nucleoprotein, which prevents DNA rereplication by directly binding to and inhibiting the DNA replication licensing factor, Cdt1. In this study, we have identified 2 Geminin genes, BmGeminin1 and BmGeminn2, in silkworm, Bombyx mori . These genes contain the Geminin conserved coiled-coil domain and are periodically localized in the nucleus during the S-G2 phase but are degraded at anaphase in mitosis. Both BmGeminin1 and BmGeminin2 are able to homodimerize and interact with BmCdt1 in cells. In addition, BmGeminin1 and BmGeminin2 can interact with each other. Overexpression of BmGeminin1 affects cell cycle progression: cell cycle is arrested in S phase, and RNA interference of BmGeminin1 leads to rereplication. In contrast, overexpression or knockdown of BmGeminin2 with RNAi did not significantly affect cell cycle, while more rereplication occurred when BmGeminin1 and BmGeminin2 together were knocked down in cells than when only BmGeminin1 was knocked down. These data suggest that both BmGeminin1 and BmGeminin2 are involved in the regulation of DNA replication. These findings provide insight into the function of Geminin and contribute to our understanding of the regulation mechanism of cell cycle in silkworm.